An artefact in celphos poisoning - A Case Report - Padmanaathan J; Mahesh Meena; Sufa Ali; Juthika Kumbhakar (Asia Pacific Journal of Medical Toxicology, 2024)
Introduction: Postmortem artefacts are changes that occur in a body after death, but before the autopsy, which can sometimes lead to misinterpretation of autopsy findings. These artefacts can result from various factors such as environmental conditions, the body's position, medical interventions before death, or the decomposition process. In this article we explain an artefact encountered in a case of Celphos poisoning. Case Presentation: A 54-years-old man, a daily wage worker, brought to GTB Hospital with alleged history of ingestion of 2 tablets of Celphos and got admitted, gastric lavage was done and expired during course of treatment. In postmortem examination, stomach contained blackish fluid along with whitish oval shaped solid matter. In mortuary, dead bodies were stored in proper refrigerated storage cabinets/shelves or cold chambers. Due to that, coconut oil, which was used for resuscitation got frozen in stomach and remained in solid state. Conclusion: Coconut oil was an iatrogenic artefact in this case. This indicates that these artefacts are present in significant number of cases, which may lead to misinterpretation of findings as evidence of underlying assault or accident if autopsy surgeon is not aware of these artefacts. Accurate interpretation is needed before labelling such findings as proofs of assault, accident or an artefact.